SOSIALISASI PROGRAM KEBIJAKAN PEMERINTAH DALAM PERLINDUNGAN DAN KONSERVASI HUTAN UNTUK REHABILITASI HABITAT SATWA KERA DIKAWASAN SEMPOR UTARA (Universitas Wijayakusuma Purwokerto, 2023)
The decline of protected wild animals into residents' settlements is not without reason. There are many cases when wild animals that previously lived in the forest suddenly descended on the majority of residents' settlements due to the destruction of their original habitat. The Director General of Conservation of Natural Resources and Ecosystems (KSDAE) of the Ministry of Environment and Forestry (KLHK) Wiratno revealed that one of the reasons for the decline of wild animals from forests to residential areas was the destruction of their 'home' habitat. One of them happened to The long-tailed macaque is very troubling and disrupting the activities of the people of Sempor Village, Sempor District, Kebumen Regency. These monkeys often enter people's settlements in the morning and evening to find food and the impact is that agricultural products from residents are stolen and the monkeys do not hesitate to disturb residents, especially women. The community is confused about how to deal with this problem because the lack of public knowledge means that these protected animals must receive a number of injuries, presumably due to residents' self-defense behavior when dealing with animals coming from the forest. From there, it was necessary to hold counseling to overcome the problem of the monkeys descending into settlements which disturbed the people of Sempor Village due to their habitat being damaged. The Ministry of Environment and Forestry continues to make various efforts to resolve animal vs human conflicts. These include reducing the rate of forest destruction, maintaining habitat and wildlife populations, preventing the expansion of forest clearing, especially in conservation forest areas, protected forests and other local protected areas which result in habitat fragmentation and disturbance. The need for public understanding of legal sanctions in the event of damage to the environment and law enforcement is also upheld..